Fluorescence spectroscopy for analysing deterioration of palm olein in batch deep-fat frying - Ibrahim, N. U. A.; Abd Aziz, Samsuzana; Zude, M.; Hashim, N. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Palm olein has been commercially used as frying medium in batch deep-fat frying. During frying, the oil usually deteriorates due to the exposure to high temperature. In this study, a fluorescence spectroscopy technique was applied to monitor the deterioration of refined, bleached, and deodorized palm olein (RBDPO) in batch deep-fat frying. 22.5 kg of French fries were used as the frying material. In 30 batches, the french fries were intermittently fried at 185 ± 5°C for eight hours a day over five consecutive days capturing 40 hours. The fluorescence intensity of the RBDPO was recorded with excitation at 390 nm and resulting emission of 465 nm. The fluorescence intensity of the RBDPO over five days of frying decreased considering the wavelength range of emission 430-640 nm and excitation 360-430 nm. The decreased in intensity of fluorescence emission and excitation spectra were inversely correlated with the FFA content of the oil samples. This study demonstrates the potential of fluorescence spectroscopy in monitoring the deterioration of RBDPO during batch deep-fat frying.